A jornada da donzela-guerreira em Memorial de Maria Moura, de Rachel de Queiroz - Mendes, Laís Sauerbronn Silva (2022)
Transiting throught the masculine and the feminine, the ambiguous figure of the maidenwarrior, present in the history and mythology of numerous cultures, despite its multiple and diverse representations, has always symbolized a break in the paradigms imposed by the social roles defined for men and women. In Brazilian literature, this ancient female archetype was portrayed as a role that often had a minor importance until the publication of Memorial de Maria Moura, a novel by Rachel de Queiroz from Ceará. The writer created in her last novel the fearless Maria Moura, a woman who takes the controll of her life, being the protagonist and narrator of her own memories. Through the analysis of the Heroine’s journey, elaborated by american theorist Maureen Murdock, together with the literary studies of Walnice Nogueira Galvão, this dissertation searched, through a feminist literary criticism, to elaborate an investigation that would not only indicate which are the characteristics of each theory that are present in the trajectory and construction of the main character of Memorial de Maria Moura, but could also question the portrayal of male and female roles within literature and how it is influenced by social norms. To accomplish this chore, after the necessary reading for the conclusion of the study, a research was developed and divided into four chapters: the first two, presenting the concepts of Murdock and Galvão; the third and fourth, performing a detailed investigation of the chosen work, defining the attributes proposed by the initial hypothesis and reinforcing the debate on the issue of the representation of gender roles within literary narratives